Measurement of the transverse momentum spectra of weak vector bosons produced in proton-proton collisions at root s=8TeV - Khachatryan, V. (2017)
The transverse momentum spectra of weak vector bosons are measured in the CMS experiment at the LHC. The measurement uses a sample of proton-proton collisions at root s = 8TeV, collected during a special low-luminosity running that corresponds to an integrated luminosity of 18: 4 +/- 0: 5 pb(-1). The production of W bosons is studied in both electron and muon decay modes, while the production of Z bosons is studied using only the dimuon decay channel. The ratios of W- to W+ and Z to W di ff erential cross sections are also measured. The measured di ff erential cross sections and ratios are compared with theoretical predictions up to next-to-next leading order in QCD.